Performance Evaluation for Mechanical Behaviour of Concrete Incorporating Recycled Plastic Bottle Fibers as Locally Available Materials - Haque, Md Rashedul; Mostafa, Md Shakil; Sah, Sujit Kumar (Civil Engineering Journal, 2021)
The objective of the study is to investigate the influence of Polyethylene Terephthalate (PET) recycled plastic bottle fibers on the compressive strength and cracking of concrete. In this study, two types of fiber are used: straight and zigzag fibers whose length and aspect ratio are 40 mm and 40 respectively. 0, 0.75, and 1.25% volume fractions of fibers replacing the volume of coarse aggregates are used in this investigation. According to ACI 211.1-91, design mixing ratio 1:2:3 for M20 concrete and water-cement ratio 0.58 are used. Curing is done in field condition and weathering action is allowed in curing time. The destructive compressive strength test shows that the compressive strength of plain concrete is 19.84 MPa, at 0.75 and 1.25% replacement for concrete with straight fibers are 19.54 and 18.84 MPa, and at 0.75 and 1.25% replacement for concrete with zigzag fibers are 18.49 and 15.69 MPa. The non-destructive compressive strength test shows that the compressive strength of plain concrete is 13.58 MPa, at 0.75 and 1.25% replacement for concrete with straight fibers are 10.36 and 8.82 MPa, and at 0.75 and 1.25% replacement for concrete with zigzag fibers are 8.21 and 8.10 MPa. The use of fibers changes the failure mode. The addition of fibers decreases the workability and cracking of concrete. Zigzag fiber slightly shows interlocking property with concrete. The addition of PET plastic fibers increases the ductility of concrete.Â Doi: 10.28991/cej-2021-03091684 Full Text: PDF